The Application of Numerical Modelling to the Assessment of the Potential for, and the Detection of, Spontaneous Combustion in Coal Mines (The Australasian Institute of Mining and Metallurgy, 2005)
pNumerical modelling has been used to examine the relationship between the results of two commonly used methods of assessing the propensity of coal to spontaneous combustion, the R70 and Relative Ignition Temperature tests, and the likely behaviour in situ. The criticality of various parameters has been examined and a method of utilising critical self-heating parameters has been developed. This study shows that on their own, the laboratory test results do not provide a reliable guide to in situ behaviour but can be used in combination to considerably increase the ability to predict spontaneous combustion behaviour./p